2019
DOI: 10.1096/fj.201901255r
|View full text |Cite
|
Sign up to set email alerts
|

A modified cholera toxin B subunit containing an ER retention motif enhances colon epithelial repair via an unfolded protein response

Abstract: Cholera toxin B subunit (CTB) exhibits broad-spectrum biologic activity upon mucosal administration. Here, we found that a recombinant CTB containing an endoplasmic reticulum (ER) retention motif (CTB-KDEL) induces colon epithelial wound healing in colitis via the activation of an unfolded protein response (UPR) in colon epithelial cells. In a Caco2 cell wound healing model, CTB-KDEL, but not CTB or CTB-KDE, facilitated cell migration via interaction with the KDEL receptor, localization in the ER, UPR activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 73 publications
2
43
0
Order By: Relevance
“…The principal virulence factor of Vibrio cholerae is cholera toxin (CT), which is comprised of a toxic A subunit and a non-toxic homopentameric B subunit (CTB). Recently, we have shown that a recombinant variant of CTB containing a KDEL endoplasmic reticulum (ER) retention motif (CTB-KDEL) has the ability to induce mucosal healing, facilitate colon epithelial wound repair, and enhance recovery from an acute dextran sulfate sodium (DSS) colitis model in mice [1,2]. These effects were attributed to the addition of the C-terminal ER retention motif, KDEL, to CTB.…”
Section: Introductionmentioning
confidence: 99%
“…The principal virulence factor of Vibrio cholerae is cholera toxin (CT), which is comprised of a toxic A subunit and a non-toxic homopentameric B subunit (CTB). Recently, we have shown that a recombinant variant of CTB containing a KDEL endoplasmic reticulum (ER) retention motif (CTB-KDEL) has the ability to induce mucosal healing, facilitate colon epithelial wound repair, and enhance recovery from an acute dextran sulfate sodium (DSS) colitis model in mice [1,2]. These effects were attributed to the addition of the C-terminal ER retention motif, KDEL, to CTB.…”
Section: Introductionmentioning
confidence: 99%
“…Upon ER localization, CTB-KDEL induced an unfolded protein response (UPR) and subsequent TGFβ signaling. In particular, the inositol-requiring enzyme 1 (IRE1)/X-box binding protein 1 (XBP1) arm of the UPR was indispensable for wound healing activity[147]. These findings were corroborated in primary mouse colon epithelial cells, where CTB-KDEL induced an UPR, while CTB and the non-GM1 binding mutant G33D-CTB-KDEL failed to exhibit such an effect.…”
mentioning
confidence: 89%
“…These findings were corroborated in primary mouse colon epithelial cells, where CTB-KDEL induced an UPR, while CTB and the non-GM1 binding mutant G33D-CTB-KDEL failed to exhibit such an effect. Moreover, in an ex vivo experiment using colectomy tissue from inflammatory bowel disease (IBD) patients, CTB-KDEL, but not CTB, induced an UPR, upregulated wound healing pathways, and maintained viable crypts[147]. These findings provide implications for the potential use of CTB-KDEL in the treatment of IBD.…”
mentioning
confidence: 95%
See 2 more Smart Citations